KAZAKH-CHINESE COOPERATION WITHIN THE FRAMEWORK OF THE PROJECT «ONE BELT, ONE ROAD» (Journal of Oriental Studies, 2018)
The history of relations between the two states is deep. Today, these relations are dynamically developing in all directions. The development of multilateral strategic partnership with China is one of the main priorities of Kazakhstan’s foreign policy. A new stage of relations between Kazakhstan and China is full of new projects in all spheres of bilateral cooperation. One such project is the one belt one road initiative, which includes the initiative of the President of the Republic of Kazakhstan Nursultan Nazarbayev on the new economic policy of Nurly Zhol and the two strategic projects of President Xi Jinping of China, the «Economic belt of the Silk Road» and the «Silk Road» in the 21st century. « This study shows the impact of this project on Kazakh-Chinese cooperation.